Local Wisdom in Algorithms: The Epistemology of Guidance Career Skills, Cultural Values, and the Dialectic of Humans with Artificial Intelligence - Carissa Nanda Wahyu Faatihah; M. Khoirudin Jalil (PSDKU Guidance and Counseling, Universitas Negeri Surabaya, 2026)
This study aims to explore in depth the epistemology of career skills from a phenomenological perspective in which artificial intelligence (AI) dominates. The background of this study is based on a fundamental shift in the way knowledge and expertise are formed and interpreted in the modern job market, which is increasingly influenced by AI. Specifically, this article investigates how individuals interpret and internalize their career knowledge amid the availability of AI-powered algorithms and platforms. Using interpretive phenomenology, this study involved in-depth interviews with six professionals across sectors who rely on AI in their daily work. Participants were selected through purposive sampling. Data analysis was conducted using Colaizzi's framework, which focuses on identifying essential themes from participants' life experiences. Results show that interaction with AI has created a